Pelatihan Ekonomi Kreatif Pembuatan Wine Salak Nanas dan Rempah-Rempah Sebagai Peluang Usaha - Mario Nikolaus Dalengkade; Bayu Achil Sadjab; Dwi Rahayu Pujiastuti; Kurnia Kurnia; Nining Purwaningsih (Parta: Jurnal Pengabdian Kepada Masyarakat, 2023)
The new economic era demands creativity that exceeds common expectations. Creative economy training such as processing pineapple, snake fruit and spices agricultural produce into wine is a breakthrough solution in increasing the economic value of a product. This insight is needed by generation Z who are leaning towards the creative economy era. The community service method covers two parts. The first is wine making training and the second is organoleptic testing of wine products. During the training process the participants were very enthusiastic in learning how to make snake fruit wine, pineapple and spices with being active in practicing and following each stage. The average results of the organoleptic test based on the level of preference for taste, aroma and color, the panelists liked the spiced wine the most by 4.73, 4.57 and 4.20 respectively. This activity was able to grow, motivate and add insight to participants in processing pineapples, snake fruit and spices into wine products as a business opportunity in the creative economy sector.